Multiple extracorporeal shock wave therapy degrades capsular fibrosis after insertion of silicone implants - Fischer, Sebastian; Hirche, Christoph; Germann, Günter; Reichenberger, Matthias (Ultrasound in medicine & biology, 2015)
Capsular fibrosis is the most frequent long-term complication after insertion of silicone devices. Today, mainly direct immunostimulation and subclinical infection are held responsible for inducing and maintaining inflammatory reactions, which lead to overwhelming extracellular matrix formation. Extracorporeal shock waves (ESWs) are capable of inhibiting inflammatory processes and revealing antibacterial capacity. In our previous study, we observed decelerated capsule development after application of a single shock wave immediately after surgery. The purpose of this study was to evaluate the effects of multiple ESWT after insertion of silicone implants in the same rodent model. Therefore, silicone prostheses were inserted into a submuscular pocket in 12 additional male Lewis rats, and shock waves were administered over a 14-d interval. At 35 d (n = 6) and 100 d (n = 6) after insertion, silicone implants and surrounding capsule tissue were removed and prepared for histologic and immunohistochemical analysis, as well as polymerase chain reaction (Ccl2, CD68, transforming growth factor β1, matrix metalloproteinase 2). Compared with the control group, multiple ESWT had no effect on day 35, but resulted in a significantly thinner capsule on day 100 (825.8 ± 313.2 vs. 813.3 ± 47.9, p = 0.759, and 1062.3 ± 151.9 vs. 495.4 ± 220.4, p < 0.001, respectively). The capsule was even thinner than after a single shock wave application, which had been found to result in thinner capsules at every time point in our previous study. This active degradation of the fibrous envelope caused by multiple ESWs was accompanied by synergistic alterations in pro- and anti-fibrotic proteins (transforming growth factor β1 and matrix metalloproteinase 2, respectively). In conclusion, after insertion of silicone devices, single ESWT is capable of decelerating capsule formation in contrast to multiple ESWT, which degrades fibrotic tissue. These findings seem to be associated with inhibition of inflammation and beneficial effects on pro- and anti-fibrotic proteins.
Gesehen am 03.08.2021